2009
DOI: 10.1097/icb.0b013e3181658ca8
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman Disease With Ocular Involvement: A Clinicopathologic Case Report

Abstract: To our knowledge, this is the first clinicopathologic report of multicentric Castleman disease involving the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…CD rarely leads to direct involvement of the orbit or ocular structures due to a lack of lymphoid tissue in the eye [10]. Several investigators have reported rare intraocular involvement [7][8][9][10][11][12]; however, the pathogenic mechanism of ocular involvement is not fully understood. We report a case of hypertensive choroidopathy in a patient with CD associated with malignant hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD rarely leads to direct involvement of the orbit or ocular structures due to a lack of lymphoid tissue in the eye [10]. Several investigators have reported rare intraocular involvement [7][8][9][10][11][12]; however, the pathogenic mechanism of ocular involvement is not fully understood. We report a case of hypertensive choroidopathy in a patient with CD associated with malignant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The choroidopathy seen in this case was thought to be caused by rapid changes in blood pressure due to malignant hypertension. Emerson et al reported choroidal invasion in a patient with CD [ 9 ]. The yellow exudative lesion on the RPE in this case was initially suspected to be caused by direct infiltration of the choroid associated with CD [ 2 , 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ophthalmic complications in MCD are very rare with most published cases describing intraorbital and optic nerve lesions 2,3. Intraocular involvement is rarer with one published adult case of uveitis,4 two cases of bilateral,5,6 one case of unilateral serous retinal detachment and choroidal effusion,7 one case of hypertensive choroidopathy,8 one case of choroidal infiltrates,7 and one case of optic nerve drusen and peripapillary choroidal neovascularization in a patient with peripheral neuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, skin changes (POEMS) syndrome and associated Castleman’s disease 9. One pediatric case describing venous engorgement and tortuosity, intraretinal hemorrhages, cotton wool spots, and neurosensory detachment of the posterior pole was thought to be due to hyperviscosity syndrome which responded to one session of plasmapheresis 10.…”
Section: Discussionmentioning
confidence: 99%
“…Orbital involvement such as bilateral enlargement of lacrimal gland and localized orbital soft tissue mass has also been reported [3]. In literature, there was one reported case of bilateral serous retinal detachment and punctate retinal pigment epithelium (RPE) epitheliopathy due to direct tumorous choroidal involvement [4], which was demonstrated histopathologically in another case report of a 69-year-old man with lymphadenopathy and bilateral choroidal infiltrates [5]. We herein report a patient with Castleman's disease who, during the course of the disease, developed hypertensive choroidopathy mimicking direct tumor involvement of choroid.…”
mentioning
confidence: 91%